1990
DOI: 10.1507/endocrine1927.66.1_50
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Glucocorticoid-Responsive Hyperaldosteronism : Follow-up Study for 21 Years

Abstract: A study of the pathophysiology in our previously reported case of glucocorticoid-responsive hyperaldosteronism (Case E.H., 17 yrs old, female; JCEM, 28: 1807, 1968), who had undergone a long-term successful treatment for 21 yrs of daily 0.5 mg dexamethasone (Dex), suggested again that the patient had 17 alpha-hydroxylase deficiency (17-OH-D) in the adrenal with minimum enzyme deficiency in the ovary. When Case E.H. was injected with zinc-ACTH for 3 days with daily 0.5 mg Dex administration, plasma levels of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The following search strategy was applied to all 5 databases: “glucocorticoid-remediable aldosteronism” OR “familial hyperaldosteronism type 1” OR “dexamethasone-suppressible hyperaldosteronism” OR “dexamethasone-suppressible aldosteronism” OR “glucocorticoid-suppressible aldosteronism” OR “glucocorticoid-suppressible hyperaldosteronism” OR “glucocorticoid-remediable hyperaldosteronism.” Search limits to “human” or “humans” studies were employed. The earliest case reports and series of cases with FH1 described before commonly used nomenclature were manually added alongside follow-up papers 13–16 after review and verification of reference lists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following search strategy was applied to all 5 databases: “glucocorticoid-remediable aldosteronism” OR “familial hyperaldosteronism type 1” OR “dexamethasone-suppressible hyperaldosteronism” OR “dexamethasone-suppressible aldosteronism” OR “glucocorticoid-suppressible aldosteronism” OR “glucocorticoid-suppressible hyperaldosteronism” OR “glucocorticoid-remediable hyperaldosteronism.” Search limits to “human” or “humans” studies were employed. The earliest case reports and series of cases with FH1 described before commonly used nomenclature were manually added alongside follow-up papers 13–16 after review and verification of reference lists.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1578 studies were identified, and 928 duplicates were removed (Figure). With the addition of the earliest studies describing patients with FH1 before diagnostic nomenclature and their follow-up articles, [13][14][15][16] 654 unique studies were identified for screening. Title and abstract screening excluded an additional 527 articles.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation